Study of Association of C-Reactive Protein with Coronary Collateral Development - Majumder, AAS; Karim, MF; Rahman, MA; Uddin, MAFK (Cardiovascular Journal, 2010)
Background: In vitro studies have shown that C-reactive protein (CRP) attenuates nitric oxide production and inhibits angiogenesis, which may result in impaired collateral development. The aim of this study was to investigate the association between CRP levels and the extent of coronary collaterals. Materials and methods: A total of 100 patients who had a stenosis of >95% in any major coronary artery in angiograms were included in the study. The CRP was measured from a venous blood sample with a high-sensitivity assay. Collaterals of the epicardial coronary arteries were then studied and graded in a scale of 0 - 3 according to Rentrop classification. Results: Mean age was 49.6 years and 86% were male. The mean CRP level was found 15.57 ±12.85 mg/L in grade 0 (n =25 ), 11.38± 11.11 mg/L in grade I( n=20 ), 9.22± 10.15 mg/L in grade II ( n=34 ) and 8.97±8.44 mg/L in grade III (n =21) collateral group. The mean CRP values reduced significantly (p<0.05) as the Rentrop collateral grade increased which indicated that patients with a higher grade of collaterals significantly had less CRP. Subjects with a higher grade of collaterals were significantly less likely to have diabetes mellitus [odds ratio (OR): 0.53, 95%; CI: 0.13, 0.91] or acute coronary syndrome [ odds ratio (OR) :0.67 , 95%; CL 0.43, 0.95] or higher CRP values [odds ratio (OR) 0.56 per 10 unit increase, 95%; CL 0.22, 0.92] but they were more likely to have higher number of vessels with significant stenosis [odds ratio (OR) : 1.59 ; 95% CI: 1.34, 1.87]. After adjusting for age, gender, clinical presentation with acute coronary syndrome, diabetes mellitus and the number of vessels with significant stenosis, each 10-unit increase in CRP values corresponded to 39% reduced- odds of having a higher collateral grade ( OR: 0.61, 95%: CL0.1 1,0.68). Conclusion: It may be concluded that elevated levels of CRP are significantly and inversely associated with angiographically visible coronary collateral development assessed by Rentrop classification. Keywords: Coronary artery disease; C-reactive protein; Coronary colletarals DOI: 10.3329/cardio.v3i1.6423 Cardiovasc. j. 2010; 3(1): 26-32